Architect and Empathy : The Importance of Human Experience in Architectural design - Arga Patria Dranie Putra (International Journal of Built Environment and Scientific Research, 2018)
Architecture usually pursued as response to human needs, a need for shelter, security, fellowship, etc. For the last couple decades the critisism to architecture for being emotionally cold starts to emerge, acused of creating distance between human from the life. As Jullio Pallasma said, the emotional coldness might be caused by the adoption of formalist attitude since the industrial revolution. Modernism argueably, have brought an ideology which focused on function and aesthetic into architecture, but the notion also resulting a far less empathic architectural. Building become apathic, as function and aesthetic pushed aside the lifeliness context. Designs are becoming less authentic, as architects prefer to use existing data to save their time. In short, it can be said that the presence of empathy have far being less acknowledged as an important aspect in architecture. To adress the notion of the problems, This paper will examine the terms of empathy, As understanding the terms would provide more information about how it could relates to architecture. Further extensions of the notion will be explored, based on the exisiting presedences which already points out the presence of empathy related topics in architecture . The paper will later examine the relevance of these examples to architecture and claim what defines the scope of “empathy” in this particular context to helps understand it’s potential use in architecture.